Polyester urethane urea (PEUU) functionalization for enhanced anti-thrombotic performance: advancing regenerative cardiovascular devices through innovative surface modifications - Rodríguez-Soto, María A.; Suárez Vargas, Natalia; Ayala-Velásquez, María; Aragón-Rivera, Andrés M.; Ostos, Carlos; Cruz, Juan C.; Muñoz Camargo, Carolina; Kim, Seungil; D’Amore, Antonio; Wagner, William R.; Briceño, Juan C. (Frontiers in Bioengineering and Biotechnology, 2023)
Thrombogenesis, a major cause of implantable cardiovascular device failure, can be addressed through the use of biodegradable polymers modified with anticoagulating moieties. This study introduces a novel polyester urethane urea (PEUU) functionalized with various anti-platelet deposition molecules for enhanced antiplatelet performance in regenerative cardiovascular devices. PEUU, synthesized from poly-caprolactone, 1,4-diisocyanatobutane, and putrescine, was chemically oxidized to introduce carboxyl groups, creating PEUU-COOH. This polymer was functionalized in situ with polyethyleneimine, 4-arm polyethylene glycol, seleno-L-cystine, heparin sodium, and fondaparinux. Functionalization was con-firmed using Fourier-transformed infrared spectroscopy and X-ray photoelectron spectroscopy. Bio-compatibility and hemocompatibility were validated through metabolic activity and hemolysis assays. AntiThe anti-thrombotic activity was assessed using platelet aggregation, lactate dehydrogenase activation assays, and scanning electron microscopy surface imaging. The whole-blood clotting time quantification assay was employed to evaluate This is a provisional file, not the final typeset article anticoagulation properties. Results demonstrated high biocompatibility and hemocompatibility, with the most potent anti-thrombotic activity observed on pegylated surfaces. However, seleno-L-cystine and fondaparinux exhibited no anti-platelet activity. The findings highlight the importance of balancing various factors and addressing challenges associated with different approaches when developing innovative surface modifications for cardiovascular devices.